2012
DOI: 10.2135/cropsci2012.04.0242
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Mycosphaerella Blight Resistance in Wild Pisum Species for Use in Pea Breeding

Abstract: Mycosphaerella blight caused by Mycosphaerella pinodes (Berk, and Blox.) Vestergren is the most important disease of pea (Pisum sativum L.) in the world. It reduces seed yield and quality and limits the areas where field pea can effectively be grown.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 33 publications
0
20
1
Order By: Relevance
“…Pea geneticists and breeders have attempted to use wild Pf for cultivar improvement, mainly for introducing disease and pest resistance alleles (Clement et al, 2009; Jha et al, 2012; Kosterin, 2016). Most wild pea accessions in germplasm banks represent random sampling, rather than systematic collections.…”
Section: Discussionmentioning
confidence: 99%
“…Pea geneticists and breeders have attempted to use wild Pf for cultivar improvement, mainly for introducing disease and pest resistance alleles (Clement et al, 2009; Jha et al, 2012; Kosterin, 2016). Most wild pea accessions in germplasm banks represent random sampling, rather than systematic collections.…”
Section: Discussionmentioning
confidence: 99%
“…The same P. humile germplasm line (P665) that carries the Mycosphaerella pinodes resistance alleles was also found to be resistant to the parasitic weed broomrape ( Orobanche crenata) (Fondevilla et al 2010). Jha et al (2012) screened wild Pisum material against Mycosphaerella pinodes isolates and identified a wild accession of this species as a promising donor of resistance alleles. Carillo et al (2013) characterized the mechanisms of response to this fungal pathogen in several wild Pisum accessions compared with susceptible domesticated check varieties.…”
Section: Pisum Sativum Ssp Humilementioning
confidence: 99%
“…syriacum using mainly AFLP, RAPD, and SSR markers (Tar'an et al, 2003; Prioul et al, 2004; Fondevilla et al, 2008). Accession P651 utilized in this research was the most promising for resistance breeding, as it had a relatively low disease score under field, as well as greenhouse, conditions (Jha et al, 2012). Earlier, Fondevilla et al (2005) observed that P651 ( P. fulvum ) had the highest level of resistance to P. pinodes , followed by P670 ( P. sativum ssp.…”
Section: Discussionmentioning
confidence: 99%